Response to cocaine, alone and in combination with methylphenidate, in cocaine abusers with ADHD - Collins, Stephanie L.; Levin, Frances R.; Foltin, Richard W.; Kleber, Herbert D.; Evans, Suzette M. (Drug and alcohol dependence, 2006)
Attention deficit hyperactivity disorder (ADHD) is prevalent in adult cocaine abusers. Yet, it remains to be determined how the response to cocaine differs in cocaine abusers with ADHD compared to cocaine abusers without ADHD. Further, since ADHD is commonly treated with stimulants, such as methylphenidate (MPH), it is important to examine whether MPH maintenance alters the response to cocaine in cocaine abusers with ADHD. Thus, the first phase of this study compared the response to cocaine in adult cocaine abusers with ADHD to those without ADHD. The second phase assessed the effects of oral sustained-release methylphenidate (MPH-SR) maintenance (40 and 60 mg) on the response to cocaine only in those with ADHD. Cocaine abusers with ADHD ( N = 7) and without ADHD ( N = 7) who were not seeking treatment remained inpatient initially for 1 week, when the effects of cocaine alone were tested (Phase 1). Cocaine abusers with ADHD remained inpatient for an additional 3 weeks, during which the effects of cocaine during oral MPH-SR maintenance were tested (Phase 2). During cocaine fixed dosing sessions, participants received four injections of i.v. cocaine (0, 16 or 48 mg/70 kg), spaced 14 min apart. During cocaine choice sessions, participants had a choice between receiving i.v. cocaine (16 or 48 mg/70 kg) or two tokens, each exchangeable for US$ 2. Subjective effects related to ADHD symptoms (e.g. ratings of “Able to Concentrate”) were significantly lower in cocaine abusers with ADHD compared to those without ADHD when placebo cocaine was administered. Active cocaine produced similar increases in cardiovascular and positive subjective effects in both groups and there was no difference in cocaine choice between the two groups. These data suggest that the response to cocaine is not different between cocaine abusers with ADHD compared to those without ADHD. When the cocaine abusers with ADHD were maintained on MPH-SR, cardiovascular effects were increased, however, this did not warrant termination of any test session. Maintenance on MPH-SR decreased some of the positive subjective effects of cocaine. Further, maintenance on a high dose of MPH-SR decreased cocaine choice. Thus, oral MPH-SR is safe in combination with repeated cocaine doses and decreases some of the positive and reinforcing effects of cocaine in cocaine abusers with ADHD.